The Palgrave Handbook of Youth Mobility and Educational Migration - Cairns, D. (2021)
This handbook provides an overview of developments in the youth mobility and migration research field, with specific emphasis on movement for education, work and training purposes, encompassing exchanges sponsored by institutions, governments and international agencies, and free movement. The collection features over 30 theoretically and empirically-based discussions of the meaning and key aspects of various forms of mobility as practiced in contemporary societies, and concludes with an exploration of the costs and benefits of moving abroad to individuals and societies at a time when the viability of free circulation is being called into question. The geographical scope of the book covers Europe, Asia, Australia and the Americas, and takes into account socio-economic and regional inequalities, as well as recent developments such as the refugee crisis, Brexit and the Covid-19 pandemic. The book integrates the fields of youth mobility and migration studies, creating opportunities for the establishment of a new paradigm for understanding the spatial circulation of youth and young adults in the twenty-first century.